2015
DOI: 10.1039/c5ew00112a
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of sludge decomposition and hydrogen production from waste activated sludge in a microbial electrolysis cell with cheap electrodes

Abstract: Low hydrogen production from anaerobic digestion of sludge has greatly limited the application of biological hydrogen-producing technology. An Fe/graphite electrode was installed into an anaerobic digester to enhance the hydrogen production from waste sludge in this study. The electrode accelerated the decomposition of the sludge, and the production of short-chain fatty acids was 3.5 folds of that in a control anaerobic reactor with no electrode. The hydrogen production was 90.6 mL g VSS −1, while it was almos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 37 publications
3
8
0
Order By: Relevance
“…Better performance was seen within 10°C to 20°C, thereby showing the advantages of MEC over other fermentative biohydrogen production processes. Again, an increasing H 2 yield with increasing external applied voltage was reported in the literature [108,113].…”
Section: Bioelectrochemical Systemsupporting
confidence: 69%
See 1 more Smart Citation
“…Better performance was seen within 10°C to 20°C, thereby showing the advantages of MEC over other fermentative biohydrogen production processes. Again, an increasing H 2 yield with increasing external applied voltage was reported in the literature [108,113].…”
Section: Bioelectrochemical Systemsupporting
confidence: 69%
“…Some common pure chemical substrates used are butyrate, glucose, acetate and glycol. However, different waste streams like poultry farming wastewater [108,109], domestic wastewater [105,110,111], waste activated sludge [112][113][114] and industrial wastewater [115,116] are used in MEC. Tenca et al [116] found a higher H 2 yield for methanolrich industrial wastewater compared with food processing wastewater, but the food processing wastewater was found to have high H 2 selectivity of around 86% compared with that of industrial chemical wastewater.…”
Section: Bioelectrochemical Systemmentioning
confidence: 99%
“…Feng et al [59] reported increase in CH4 production and WAS degradation rate by 22% and 11%, respectively at an applied voltage of 0.3 V. However, lower CH4 production and WAS degradation was observed at applied voltage of 0.6 V, and the authors contributed this to the excessive utilization of H + in the cathode causing pH increase to inhibit methanogenesis. This finding was further confirmed by the same research group in a follow-up study [60], where increase in cathodic pH (9.5) due to proton consumption inevitably inhibited methanogenesis. The influence of applied voltage (0.3 and 0.6 V) on methanogenic population in MEC-AD system was investigated in another study, and 17.2 times increase in abundance of hydrogenotrophic methanogens was observed at low (0.3 V) applied voltage with enhanced (8-9%) CH4 production [61].…”
Section: New Applicationintegration Of Mec With Fermentation For Cellsupporting
confidence: 60%
“…One new and important application of MECs is the addition of electrodes directly into an anaerobic digester, in order to improve performance and increase the methane concentration in the product gas78910. Such an integration is not practical using MFCs as the anaerobic digestion (AD) process requires oxygen free environment.…”
mentioning
confidence: 99%